Analisis Perancangan Fractional Frequency Reuse Pada Jaringan Long Term Evolution Di Kota Pekanbaru - Makmul Siddiq Harahap; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Long Term Evolution - Advanced (LTE-A) is a 4G wireless broadband technology based on Orthogonal Frequency Division Multiplexing (OFDM). It provides improved system capacity and coverage, high peak data rate and low latency. OFDM technology is used to reduce the Intersymbol Interference (ISI), however it increases the effect of Intercell Interference (ICI) due to single frequency used. The high ICI will give affect to the perfomance of users at the cell edge and cell centre. To avoid the ICI, the ICI management is required.In this paper, the ICI management is described. There are three schemes are analyzed such as Frequency Reuse 1 (FR1), Fractional Frequency Reuse (FFR), Soft Frequency Reuse (SFR). From the simulation results, the best results are provided by SFR. It gives CINR of 21,14 dB, and 40.547,67 kbps of throughputKeywords : LTE, SFR, FFR, Reuse 1, throughput, CINR